2004
DOI: 10.1111/j.1365-2141.2004.05189.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations within the protein Z‐dependent protease inhibitor gene are associated with venous thromboembolic disease: a new form of thrombophilia

Abstract: Summary Protein Z‐dependent protease inhibitor (ZPI) is a serpin that inhibits the activated coagulation factors X and XI. The precise physiological significance of ZPI in the control of haemostasis is unknown although a deficiency of ZPI may be predicted to alter this balance. The coding region of the ZPI gene was screened for mutations using denaturing high‐performance liquid chromatography. 16 mutations/polymorphisms within the coding region of ZPI were identified including two mutations, which generated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…[13][14][15] In conclusion, our results are consistent with the hypothesis that elevated protein Z concentrations are prothrombotic. Further advances in understanding of the underlying mechanisms of the association between protein Z and thrombosis 23 may provide new insights into the cause, pathogenesis, or prognosis of acute ischemic stroke and could potentially yield new therapeutic strategies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In conclusion, our results are consistent with the hypothesis that elevated protein Z concentrations are prothrombotic. Further advances in understanding of the underlying mechanisms of the association between protein Z and thrombosis 23 may provide new insights into the cause, pathogenesis, or prognosis of acute ischemic stroke and could potentially yield new therapeutic strategies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…PZ and ZPI deficiency have been shown to enhance thrombosis in mouse models (15, 16), but whether PZ and ZPI are involved in clinical thrombotic disease is controversial, with some, but not all, studies suggesting such a relationship (17-23). The aim of our study was to investigate the potential role of PZ and ZPI in the sepsis-associated activation of the inflammation and coagulation cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Besides inhibiting FXa, ZPI inhibits FXIa (EC 3.4.21.27) in a reaction stimulated 2-fold by heparin and not requiring protein Z (3). Recently, mutations in ZPI that generate stop codons at residues Arg-67 or Trp-303 were found to be significantly associated with venous thrombosis (6), although a different study found no association between ZPI or protein Z levels and venous thrombosis (7).…”
mentioning
confidence: 99%